Uma aplicação do EVA (Economic Value Added) para a agroindústria canavieira do Paraná - Queiroz, Susã Sequinel de (2007)
The methodology of Economic Value Added (EVA) verifies if the capital invested by the company is being paid properly, taking into account the opportunity cost of other alternative applications. This work identifies the occurrence or not of economic value creation in the plant and the results arising from the application of this methodology show the companies true profit, informing if they, through their activities, are or not creating value and adding wealthy to their owners. As corollary, it was found that according to figures calculated for the EVA, Alpha plant destroyed economic value over the six years examined. The profits generated by the assets were not sufficient to cover the increase in the cost of capital.